Does eating less make you live longer and better? An update on calorie restriction - Picca A (Dove Medical Press, 2017)
Anna Picca,1 Vito Pesce,2 Angela Maria Serena Lezza2 1Department of Geriatrics, Neuroscience and Orthopedics, Catholic University of the Sacred Heart School of Medicine, Rome, 2Department of Biosciences, Biotechnologies and Biopharmaceutics, University of Bari, Bari, Italy Abstract: The complexity of aging is hard to be captured. However, apart from its tissue-specific features, a structural and functional progressive decline of the whole organism that leads to death, often preceded by a phase of chronic morbidity, characterizes the common process of aging. Therefore, the research goal of scientists in the field moved from the search for strategies able to extend longevity to those ensuring healthy aging associated with a longer lifespan referred to as “healthspan”. The aging process is plastic and can be tuned by multiple mechanisms including dietary and genetic interventions. To date, the most robust approach, efficient in warding off the cellular markers of aging, is calorie restriction (CR). Here, after a preliminary presentation of the major debate originated by CR, we concisely overviewed the recent results of CR treatment on humans. We also provided an update on the molecular mechanisms involved by CR and the effects on some of the age-associated cellular markers. We finally reviewed a number of tested CR mimetics and concluded with an evaluation of future applications of such dietary approach. Keywords: aging, calorie restriction, studies on humans, CR molecular mechanisms, CR mimetics